Phylogenetic Characterization of Arboviruses in Patients Suffering from Acute Fever in Rondônia, Brazil - Jackson Alves da Silva Queiroz; Luan Felipo Botelho-Souza; Felipe Souza Nogueira-Lima; Rita de Cássia Pontello Rampazzo; Marco Aurélio Krieger; Miriam Ribas Zambenedetti; Fabricio Klerinton Marchini; Ivo Alberto Borghetti; Dhelio Batista Pereira; Juan Miguel Vilalobos Salcedo; Deusilene Souza Vieira; Alcione de Oliveira dos Santos (Viruses, 2020)
The purpose of the study was to classify, through phylogenetic analyses, the main arboviruses that have been isolated in the metropolitan region of Porto Velho, Rondônia, Brazil. Serum samples from patients with symptoms suggesting arboviruses were collected and tested by One Step RT-qPCR for Zika, Dengue (serotypes 1–4), Chikungunya, Mayaro and Oropouche viruses. Positive samples were amplified by conventional PCR and sequenced utilizing the Sanger method. The obtained sequences were aligned, and an evolutionary analysis was carried out using Bayesian inference. A total of 308 samples were tested. Of this total, 20 had a detectable viral load for Dengue, being detected DENV1 (18/20), co-infection DENV1 and DENV2 (1/20) and DENV4 (1/20). For Dengue serotype 3 and for the CHIKV, ZIKV, MAYV and OROV viruses, no individuals with a detectable viral load were found. A total of 9 of these samples were magnified by conventional PCR for sequencing. Of these, 6 were successfully sequenced and, according to the evolutionary profile, 5 corresponded to serotype DENV-1 genotype V, and 1 to serotype DENV-4 genotype II. In the study, we demonstrate co-circulation of the DENV-1 genotype V and the DENV-4 genotype II. Co-circulation of several DENV serotypes in the same city poses a risk to the population and is correlated with the increase of the most severe forms of the disease. Similarly, co-circulation of genetically distinct DENV and the occurrence of simultaneous infections can affect recombination events and lead to the emergence of more virulent isolates.